Peningkatan Nilai Ekonomi Tanaman Kelor Melalui Inovasi Produk Kopi Kelor Siap Saji di Desa Selengen Kabupaten Lombok Utara - Baiq Resky Tiara Anandha; Wira Parawangsa; Maiser Syaputra; Zalianty Dwinur Safitri (Universitas Mataram, 2026)
This community service activity aimed to enhance the economic value of Moringa oleifera through the development and innovation of instant moringa coffee products based on local potential in Selengen Village, Kayangan District, North Lombok Regency. The activity was conducted through the Community Empowerment Student Service Program (KKN-PMD) of the University of Mataram from December 2025 to February 2026, employing a Participatory Action Research (PAR) approach. The methods included identifying community potential and problems, forming MSME groups, providing assistance in production and product innovation, and strengthening business legality. The results showed an improvement in the knowledge and skills of MSME groups in processing moringa coffee and developing flavor variants. This program produced an innovative instant moringa coffee product with an initial production output of 100 cup units as a production trial. In addition, business licensing assistance resulted in the issuance of a Business Identification Number (NIB) for MSME actors. However, overall community involvement remained limited, indicating the need for continued assistance to support the sustainability of business development.